HOW READING ENHANCES VOCABULARY AND LANGUAGE SKILLS (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores how reading serves as a natural and effective tool for vocabulary acquisition and overall language development. It emphasizes the role of context in understanding word meanings, grammar patterns, and language style. The paper also discusses how different types of texts contribute to richer language competence.